2003
DOI: 10.1111/1467-7687.00261
|View full text |Cite
|
Sign up to set email alerts
|

German‐learning infants’ ability to detect unstressed closed‐class elements in continuous speech

Abstract: The paper reports on two experiments with the head turn preference method which provide evidence that already at 7 to 9 months, but not yet at 6 months, German-learning infants do recognize unstressed closed-class lexical elements in continuous speech. These findings support the view that even preverbal children are able to compute at least phonological representations for closedclass functional elements. They also suggest that these elements must be available to the language learning mechanisms of the child f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
98
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 25 publications
(25 reference statements)
5
98
1
4
Order By: Relevance
“…Because the function word the signals the beginning of a noun phrase, once the location of such a phrase is detected, it also helps to find the location of other elements within the same syntactic constituent ( Jusczyk, 2002). Further evidence for the connection between syntax and prosody comes, for instance, from a study with 7-to 9-month-old German infants who recognized the internal structure of a noun phrase (the + content word) in continuous speech (Höhle & Weissenborn, 2003). As for the importance of prosody in acquiring syntactic rules, Weinert (1992) showed that normal control children were able to learn the syntactic rules from prosodically enriched sentences, whereas children with developmental language impairment could not make use of the available prosodic information for the acquisition of syntactic rules.…”
Section: Introductionmentioning
confidence: 99%
“…Because the function word the signals the beginning of a noun phrase, once the location of such a phrase is detected, it also helps to find the location of other elements within the same syntactic constituent ( Jusczyk, 2002). Further evidence for the connection between syntax and prosody comes, for instance, from a study with 7-to 9-month-old German infants who recognized the internal structure of a noun phrase (the + content word) in continuous speech (Höhle & Weissenborn, 2003). As for the importance of prosody in acquiring syntactic rules, Weinert (1992) showed that normal control children were able to learn the syntactic rules from prosodically enriched sentences, whereas children with developmental language impairment could not make use of the available prosodic information for the acquisition of syntactic rules.…”
Section: Introductionmentioning
confidence: 99%
“…Shi, Werker, and Morgan (1999) found that newborns can discriminate isolated lexical words from grammatical words based on acoustic characteristics. An early awareness of the phonological characteristics of grammatical words may provide a foundation for the increasingly differentiated forms of distributional learning that begin to emerge later in the first year (e.g., Höhle & Weissenborn, 2003;Höhle, Weissenborn, Kiefer, Schulz & Schmitz, 2004). By 11 months, infants are attentive to prosodic and segmental features of functor words in fluent speech (Shady, 1996;Shafer, Shucard, Shucard, & Gerken, 1998), and by 18 months, they distinguish passages in which familiar functors are grammatically or ungrammatically positioned (Santelmann & Jusczyk, 1998).…”
mentioning
confidence: 99%
“…During the second half of their first year of life, infants can isolate elements in the speech stream that correspond to lexical items, as well as bound morphemes (e.g., Blenn, Seidl, & Höhle, 2003;Höhle & Weissenborn, 2003;Jusczyk & Aslin, 1995;Jusczyk, Houston, & Newsome, 1999). At the same time, they are able to track co-occurrence patterns between adjacent elements on the basis of distributional analyses, including order relations (Gomez & Gerken, 1999;Jusczyk, Houston, et al, 1999;Mandel, Kemler Nelson, & Jusczyk, 1996;Marcus, Vijayan, Bandi Rao, & Vishton, 1999;Saffran, 2001;Saffran, Aslin, & Newport, 1996;Saffran, Johnson, Aslin, & Newport, 1999).…”
mentioning
confidence: 99%